Unveiling the Red and Brownish-Green Polymorphs of a Novel ROY Derivative: 2-(4-((3-Cyanothiophen-2-yl)amino)-3-nitrophenyl)Acetic Acid - Nogueira, Bernardo A.; Lopes, Susana M. M.; Rodrigues, Ana Clara B.; Eusebio, M. Ermelinda S.; Andre, Vania; Duarte, Teresa; Paixao, J. A.; Melo, Teresa M. V. D. Pinho e; FAUSTO, RUI (American Chemical Society, 2024)
Polymorphism has been the subject of many studies in the last decades, including a particular type of polymorphism where the colors exhibited by the polymorphs differ. However, only relatively limited or narrow differences in color were observed in color polymorphs of the same compound. Indeed, to this date, almost all compounds known to show color polymorphism exhibit red, orange, or yellow tones, as is the case of the notable ROY molecule (5-methyl-2-[(2-nitrophenyl)-amino]-3-thiophenecarbonitrile), which is the compound with more polymorphs reported and structurally characterized hitherto. In this work, we report a new color polymorphic material derived from ROY, (2-(4-((3-cyanothiophen-2-yl)-amino)-3-nitrophenyl)-acetic acid; or ROY-CAM), synthesized for the first time by nucleophilic aromatic substitution reaction between 2-(4-fluoro-3-nitrophenyl)-acetic acid and 2-aminothiophene-3-carbonitrile, which exhibits a red (P21/n, m.p.: 184 C-degrees and theta = -4.4(degrees) and 3.0(degrees)) and a brownish-green polymorph (P1, m.p.: 190 C-degrees and theta = -66.1(degrees)). This is the first time a member of the ROY family of compounds was observed to exhibit a brownish-green polymorph and, more importantly, the first time that a molecular compound exhibits a red and a greenish polymorphs, i.e., this is the first example of an organic molecule that originates polymorphs covering such a wide range of color. The isolated molecule of ROY-CAM has 11 low-energy conformers, which were accessed by DFT calculations, with two of these conformers being identified in the observed polymorphs of the compound: in the brownish-green polymorph, the most stable conformer exists, while the red polymorph is composed of molecules assuming a conformation similar to that of the third most stable conformer. In the latter polymorph, the intramolecularly disfavored conformation assumed by the molecules is stabilized in the crystal lattice through interactions between carboxylic acid groups of neighboring molecules, resulting in dimeric units formed between pairs of the two distinct molecules that constitute the asymmetric unit of the crystal. The two identified polymorphs were characterized vibrationally (by both IR and Raman spectroscopies), and a thermal study is also presented (based on DSC, PLTM, and TGA measurements). Furthermore, the brownish-green and red colors exhibited by the polymorphs of ROY-CAM are explained based on the differences in the structures of the molecules that are present in these crystals.
Keywords: Color; Differential Scanning Calorimetry; Molecular Structure; Molecules